Total Synthesis of (+)-Alstonlarsine A: Old Reactions in Modern Alkaloids Synthesis - Ferjancic, Zorana B.; Bihelovic, Filip J. (Synlett, 2022)
(+)-Alstonlarsine A is a recently isolated monoterpenoid indole alkaloid, possessing a novel pentacyclic skeleton and interesting biological activity, making it an attractive target for synthetic chemists. In this article we focus on its total synthesis, grounded on enamine formation/Diels–Alder reaction domino sequence, as well as a novel methodology for indole C2 functionalization via carbenoid insertion, which could also allow for the synthesis of other indole alkaloids possessing cycloalka[b]indole subunits.1 Introduction2 Diels–Alder Reaction3 Methodology Studies4 Total Synthesis of (+)-Alstonlarsine A by Bihelovic and Ferjancic5 Total Synthesis of (+)-Alstonlarsine A by Zhai6 Summary
Keywords: alkaloid; Diels–Alder; domino reactions; natural products; total synthesis